Executorial Power of Constitutional Court Decisions on Legislative Follow-Up by the People's Representative Council - Rahmi Agustin; Nur Rohim Yunus (SALAM: Jurnal Sosial dan Budaya Syar-i, 2026)
This study analyzes the executive power of Constitutional Court Decision No. 135/PUU-XXII/2024 in the Indonesian general election system and the legal implications of the lack of legislative follow-up. The study focuses on the decision's final and binding nature, its non-self-executing character, and the role of legislators. This qualitative, normative-juridical research uses legislative, conceptual, and case-based approaches. Data collection was conducted through library research of relevant books, journals, and regulations, analyzed using content analysis. The results show that, despite its final and binding nature, the executive power of the decision does not always take effect immediately when it requires changes to statutory norms. The lack of legislative follow-up to Constitutional Court Decision No. 135/PUU-XXII/2024 creates legal uncertainty, weakens the effectiveness of constitutional supremacy, and has the potential to trigger constitutional issues in the implementation of elections. Therefore, it is necessary to strengthen the design of Constitutional Court decisions to make them more implementable and provide a clear legislative follow-up mechanism to ensure the effective enforcement of decisions within the Indonesian constitutional system.